Molecular phylogeny and historical biogeography of West Indian boid snakes (Chilabothrus) (2013)
The evolutionary and biogeographic history of West Indian boid snakes (Epicrates), a group of nine species and 14 subspecies, was once thought to be well understood; however, new research has indicated that we are missing a clear understanding of the evolutionary relationships of this group. Here, we present the first multilocus, species-tree based analyses of the evolutionary relationships, divergence times, and historical biogeography of this clade with data from 10 genes and 6256 bp. We find evidence for a single colonization of the Caribbean from mainland South America in the Oligocene or early Miocene, followed by a radiation throughout the Greater Antilles and Bahamas. These findings support the previous suggestion that Epicrates sensu lato Wagler is paraphyletic with respect to the anacondas (Eunectes Wagler), and hence we restrict Epicrates to the mainland clade and use the available name Chilabothrus Duméril and Bibron for the West Indian clade. Our results suggest some diversification occurred within island banks, though most species divergence events seem to have occurred in allopatry. We also find evidence for a remarkable diversification within the Bahamian archipelago suggesting that the recognition of another Bahamian endemic species C. strigilatus is warranted.